Getting palliative medications right across the contexts of homes, hospitals and hospices: protocol to synthesise scoping review and ethnographic methods in an activity theory analysis. Issue 3 (17th March 2022) - Yardley, Sarah; Francis, Sally-Anne; Dean Franklin, Bryony; Ogden, Margaret; Kajamaa, Anu; Mattick, Karen
Abstract : Introduction: Prescribing and medication use in palliative care is a multistep process. It requires systems coordination and is enacted through activities of patients, informal carers and professionals. This study compares practice to idealised descriptions of what should happen; identifying when, how and why process disturbances impact on quality and safety. Our objectives are to: Document an intended model (phase 1, scoping review). Refine the model with study of practice (phase 2, ethnography). Use the model to pinpoint 'hot' (viewed as problematic by participants) and 'cold' spots (observed as problematic by researchers) within or when patients move across three contexts-hospice, hospital and community (home). Create learning recommendations for quality and safety targeted at underlying themes and contributing factors. Methods and analysis: The review will scope Ovid Medline, CINAHL and Embase, Google Scholar and Images—no date limits, English language only. The Population (palliative), Concept (medication use), Context (home, hospice, hospital) framework defines inclusion/exclusion criteria. Data will be extracted to create a model illustrating how processes ideally occur, incorporating multiple steps of typical episodes of prescribing and medication use for symptom control. Direct observations, informal conversations around acts of prescribing and medication use, and semistructured interviews will be conducted with a purposive sample of patients, carers and professionals. Drawing on activity theory, we will synthesise analysis of both phases. The analysis will identify when, how and why activities affect patient safety and experience. Generating a rich multivoiced understanding of the process will help identify meaningful targets for improvement. Ethics and dissemination: Ethical approval granted by the Camden & Kings Cross NHS Regional Ethics Committee (21/LO/0459). A patient and public involvement (PPI) coinvestigator, a multiprofessional steering group and a PPI engagement group are working with the research team. Dissemination of findings is planned through peer-reviewed publications and a stakeholder (policymakers, commissioners, clinicians, researchers, public) report/dissemination event.